Efforts To Improve Teacher Competence In Developing Learning Implementation Plans Through Continuous Guidance - Isman Isman (Jurnal Ilmiah Pendidikan Scholastic, 2017)
To be able to learn something well, we need to hear, see, ask questions about it, and speak with others. Not only that, teachers need to "do it", that is to describe things in their own way, for example, trying to practice skills and doing tasks that demand knowledge they have gained. The problems studied in this study are: How to improve students' understanding of the lesson by learning through continuous guidance? The steps taken in improving the pretation using learning through continuous guidance?